2014
DOI: 10.1590/s0100-204x2014001000009
|View full text |Cite
|
Sign up to set email alerts
|

A adição de xisto retortado aumenta a retenção do carbono de resíduos vegetais no solo

Abstract: O objetivo deste trabalho foi avaliar o efeito de curto prazo e o residual de doses de xisto retortado (XR) sobre a retenção do C de resíduos culturais no solo. Foram avaliadas a mineralização e a retenção de C de folhas e talos de soja enriquecidos com 13C, em solo com e sem histórico de aplicação de XR e na presença e na ausência de doses crescentes de XR. Houve efeito de curto prazo do XR sobre a retenção de C no solo. Esse efeito ocorreu somente com a mistura de folhas + 3 Mg ha-1 de XR, em que a retenção … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
4
0
1
Order By: Relevance
“…The non-effect on soil chemical properties in the medium-term was somehow expected since annual carbon input by ROS application was no more than 250 kg ha À1 in the higher dose (T4). This behaviour converges with Leão et al (2014), who also did not observe changes neither in the soil OM nor in the particulate and mineral carbon fractions after ROS cumulative addition of 15 Mg ha À1 in the same soil type as the present study. Concerning to soil pH, in general it was verified that values were below 5.5 in all layers and treatments (Table 3), inadequate level for grain crops under no-tillage system in southern Brazil (CQFS, 2016), indicating that ROS was not able to influence soil pH, although its relevant concentration of calcium carbonate (Ribas et al, 2017).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The non-effect on soil chemical properties in the medium-term was somehow expected since annual carbon input by ROS application was no more than 250 kg ha À1 in the higher dose (T4). This behaviour converges with Leão et al (2014), who also did not observe changes neither in the soil OM nor in the particulate and mineral carbon fractions after ROS cumulative addition of 15 Mg ha À1 in the same soil type as the present study. Concerning to soil pH, in general it was verified that values were below 5.5 in all layers and treatments (Table 3), inadequate level for grain crops under no-tillage system in southern Brazil (CQFS, 2016), indicating that ROS was not able to influence soil pH, although its relevant concentration of calcium carbonate (Ribas et al, 2017).…”
Section: Resultssupporting
confidence: 93%
“…Therefore, ROS could play a role as a binding agent and consequently enhances soil aggregation. In a previous study, Leão et al (2014) observed a short-term effect of ROS on carbon retention when crop residues were added to the soil in association with the ROS by-product. According to Pimentel et al (2006), ROS reactivity can be linked to the presence of 2:1 clay minerals, especially illite and montmorillonite, and silanoids, as well as hydroxylic and carboxylic functional groups.…”
Section: Treatmentioning
confidence: 92%
“…Em outro estudo, foi constatado que a adição de quantidades crescentes de XR favoreceu a fixação de carbono proveniente de folhas e talos de soja em solos. 22 Cabe ressaltar também que a presença de XR em solo reduziu a emissão de CO 2 e não influenciou negativamente na atividade microbiana e enzimática do solo, pelo menos até o limite de 3 ton de XR ha -1 de solo. 23 Apesar da possibilidade de uso do XR na agricultura, é importante levar em consideração a presença de compostos orgânicos indesejá-veis que podem estar presentes no XR.…”
Section: Introductionunclassified
“…Likewise, the average mineralization of the C added to the sandy-loam soil was lower in the two treatments with additives (~9.5%), compared with the compost without them (20.5%). These results suggest that, besides soil texture, the addition of ROS to PS during composting affected the mineralization of the C from the compost, probably because the agromineral plays a similar role to clay due to its characteristics, which may help in the physical and chemical protection of organic composts (Doumer et al, 2011;Leão et al, 2014). This is possible because ROS is derived from rocks composed mainly of clay minerals, quartz, feldspars, micas, as well as pyrite and carbonates (Pimentel et al, 2006), which remain unchanged after pyrolysis (Ribas, 2012).…”
Section: Resultsmentioning
confidence: 98%
“…In the few studies conducted to date, ROS has promoted C retention in agricultural soils, protecting them from microbial attacks (Doumer et al, 2011;Leão et al, 2014), and did not increase potentially the levels of toxic elements or affect the contents of macronutrients in the soil (Martinazzo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%